2014
DOI: 10.1021/ie403097h
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer Coefficients for CO2 Absorption into Aqueous Ammonia Using Structured Packing

Abstract: In this study, the gas phase volumetric overall mass transfer coefficients (K G a e ) for CO 2 absorption into aqueous ammonia solutions were measured to explore the mass transfer performance of a column packed with structured packing. The K G a e values were evaluated over ranges of main operating variables, that are, 1400−2300 m 3 ·m −2 ·h −1 gas flow rate, 20−39 m 3 · m −2 ·h −1 liquid flow rate, up to 8 kPa partial pressure of CO 2 , and 0.27−0.72 kmol·m −3 ammonia concentration. The results show that high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 46 publications
1
13
1
Order By: Relevance
“…the gas flow rate should be kept suitable value. Similar behavior was showed by Xu et al, [33] and Li et al, [51].…”
Section: Iieffect Of Gas Flow Ratesupporting
confidence: 89%
See 1 more Smart Citation
“…the gas flow rate should be kept suitable value. Similar behavior was showed by Xu et al, [33] and Li et al, [51].…”
Section: Iieffect Of Gas Flow Ratesupporting
confidence: 89%
“…In the packed columns, the effective gas-liquid interfacial area (a v ) is considered as an important parameters in mass transfer for CO 2 absorption in addition to the mass transfer coefficients ( ). Therefore, the overall mass transfer coefficients can be given as follows [36,51]: -For the chemical absorption of CO 2 in a packed column and fast reaction where the mole fraction of CO 2 in equilibrium with the bulk liquid is assumed zero and the differential mass balance is given by Eq. 18…”
Section: Overall Mass Transfer Coefficientmentioning
confidence: 99%
“…The overall conclusion of their work was that adding NH 3 to AMP and MDEA and using structured packing produced higher K GCO 2 a V values. Li, et al 72 have performed experiments for CO 2 absorption using an NH 3 solution to determine the K GCO 2 a V values in an absorber column packed with a novel structured packing with diversion windows type. The height of the absorber column and column diameter were 2.4 m (packing height: 2 m) and 0.15 m, respectively.…”
Section: K Gco 2 Amentioning
confidence: 99%
“…Their results showed that the developed correlation had an error of 9.8% when predicting experimental data. Li, et al 72 have developed the K GCO 2 a V correlation in an absorber column packing with diversion windows type in a NH 3 -CO 2 system. The correlation is based on important parameters such as the liquid ow rate (L), NH 3 concentration and CO 2 partial pressure: K G a e ¼ 0:0767ðLÞ 0:42 ðMÞ 0:495 .…”
Section: Packing Typementioning
confidence: 99%
“…The packed bed reactors facilitate high interfacial areas using either structured packings or random packings. Structured packings are found to give higher mass transfer rates [9][10][11][12]. The efficiency of a structured packing depends majorly upon micro level interactions between gas liquid immiscible phases next to packing surface.…”
mentioning
confidence: 99%